Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
4.
a)
[tex]L=\frac{2}{8}+\frac{4}{8}=\frac{6}{8}\\\\P=\frac{1}{8}+\frac{6}{8}=\frac{7}{8}\\\\\frac{6}{8}<\frac{7}{8}[/tex]
b)
[tex]L=\frac{8}{11}+\frac{4}{11}=\frac{12}{11}=1\frac{1}{11}\\\\P=\frac{10}{11}+\frac{2}{11}=\frac{12}{11}=1\frac{1}{11}\\\\1\frac{1}{11}=1\frac{1}{11}[/tex]
c)
[tex]L=\frac{7}{9}-\frac{4}{9}=\frac{3}{9}\\\\P=\frac{7}{9}-\frac{3}{9}=\frac{4}{9}\\\\\frac{3}{9}<\frac{4}{9}[/tex]
d)
[tex]L=2-\frac{2}{5}=1\frac{3}{5}\\\\P=\frac{2}{5}+\frac{1}{5}=\frac{3}{5}\\\\1\frac{3}{5}>\frac{3}{5}[/tex]
e)
[tex]L=\frac{17}{20}-\frac{9}{20}=\frac{8}{20}\\\\P=\frac{19}{20}-\frac{11}{20}=\frac{8}{20}\\\\\frac{8}{20}=\frac{8}{20}[/tex]
f)
[tex]L=\frac{10}{13}+5\frac{5}{13}=\frac{15}{13}=1\frac{2}{13}\\\\P=\frac{7}{13}+\frac{5}{13}=\frac{12}{13}\\\\1\frac{2}{13}>\frac{12}{13}[/tex]
g)
[tex]L=1\frac{3}{4}-\frac{1}{4}=1\frac{2}{4}\\\\P=\frac{6}{4}-\frac{3}{4}=\frac{3}{4}\\\\1\frac{2}{4}>\frac{3}{4}[/tex]
h)
[tex]L=\frac{38}{100}-\frac{13}{100}=\frac{25}{100}\\\\P=\frac{33}{100}-\frac{9}{100}=\frac{24}{100}\\\\\frac{25}{100}>\frac{24}{100}[/tex]
6.
a)
[tex]\frac{11}{7}-\frac{5}{7}=\frac{6}{7}[/tex]
[tex]\frac{4}{5}-\frac{2}{5}=\frac{2}{5}[/tex]
[tex]1\frac{3}{8}+\frac{5}{8}=1\frac{8}{8}=2[/tex]
b)
[tex]2\frac{3}{4}-\frac{1}{4}-1\frac{3}{4}=2\frac{2}{4}-1\frac{3}{4}=1\frac{6}{4}-1\frac{3}{4}=\frac{3}{4}[/tex]
[tex]1-\frac{5}{7}+\frac{12}{7}=\frac{2}{7}+\frac{12}{7}=\frac{14}{7}=2[/tex]
[tex]\frac{9}{6}+\frac{3}{6}-2=\frac{12}{6}-2=2-2=0[/tex]